Diversity and distribution of macroalgae in Seagrass meadows at Taklong at Taklong Island Marine Reserve, Nueva Valencia, Guimaras. - Lastimoso, John Michael L.
Species composition, diversity, and cover of macroalgae in 3 selected seagrass meadows dominated by Thalassia hemprichii, Enhalus acoraoides, and Cymodocea rotundata in TINMR were studied in December, 2016. A total of 25 species of microalgae were recorded including 5 species of Rhodophyta, 11 species of Chlorophyta, and 9 species of Phaeophyta. Six (6) of these species were new records for the marine reserve. All sites showed relatively high diversity index (H?=1.99 to 2. 72) but low evenness (J?=0.76). Banago and Calaparan meadows were most familiar in terms of species composition. Actinotrichia fragilis, Chaetomorpha crassa, Gracilaria sp., and Turbinaria ornate were the most common species. Gracilaria sp. had the highest cover and was the most likely encountered species. Mean macroalgae cover per m2 in the 3 sites ranged from 8.39% m-2 to 13.71% m-2. In this study, relative to seagrass, macroalgae comprised a low proportion of the total marine macrophytes (19.4% to 25.5%). Eight (8) species of macroalgae in the reserve had economic importance.